Understanding user value experience in Business Campus Environments - Raulas, Liisa (My University, 2020)
The working life is undergoing drastic changes, as work is no longer taking place only in one place but instead in multiple locations and different settings. This study aims to gain understanding into how user value experience is formed in Business Campus environments which are referred to in this study as an environment, in which multiple different private or public organizations have their office facilities and that encourages networking between the people and organizations, aiming to create a networked business community within the premises. In this study the user value experience was studied through identifying sources of user value in the Business Campus environment and therefore the study adopted a customer value approach, building on theories of customer value. From the literature it was concluded that the customer is considered as the primary creator of value through value-in-use and the role of the provider in the value creation process is to act as a facilitator of customer’s own value creation. Secondly, customer value is created through a combination of both functional and hedonic aspects of the service, also referred to in the literature as extrinsic or intrinsic. Additionally, customer value can be observed through a hierarchical approach. Hence, user value experience was defined as the user’s holistic, personal, subjective and contextual perception on the use of a product, system or service that results from both pragmatic qualities and emotional and affective responses throughout the use. The five key value elements constituting to the user value experience in Business Campus environments were identified as functional value, convenience value, aesthetic value, social value and networking value. User value experience is formed as a combination of these and is a holistic concept that encompasses both extrinsic and intrinsic aspects of the working environment. Furthermore, user value experience was observed as subjective and varying between users. To highlight the varying nature of the value experience, three user personas were identified in this study; doer, multitasker and socializer. On a practical level, this study brings insight into developing Business Campus service environments.
Keywords: Business Campus, workplace user value experience